2002
DOI: 10.1046/j.1529-8027.2002.02026_12.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Arsenic Poisoning From Burning High‐Arsenic‐Containing Coal In Guizhou, China

Abstract: Arsenic is an environmental hazard and the reduction of drinking water arsenic levels is under consideration. People are exposed to arsenic not only through drinking water but also through arsenic‐contaminated air and food. Here we report the health effects of arsenic exposure from burning high arsenic‐containing coal in Guizhou, China. Coal in this region has undergone mineralization and thus produces high concentrations of arsenic. Coal is burned inside the home in open pits for daily cooking and crop drying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…Arsenic is a confirmed human carcinogen. Besides cancers such as skin and lung, induced by arsenic exposure through drinking water (Sun et al 2006), it has also been reported that arsenic exposure through coal burning can induce skin cancers (Liu et al 2002). Since oxidative stress is involved in many stages that regulate cancer development (Karihtala and Soini.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenic is a confirmed human carcinogen. Besides cancers such as skin and lung, induced by arsenic exposure through drinking water (Sun et al 2006), it has also been reported that arsenic exposure through coal burning can induce skin cancers (Liu et al 2002). Since oxidative stress is involved in many stages that regulate cancer development (Karihtala and Soini.…”
Section: Resultsmentioning
confidence: 99%
“…Since coal is plentiful in this area at the surface, burning coal has become the primary fuel source for domestic use, such as cooking, heating and drying of crops. Chronic exposure to high level of iAs through burning coal in domestic living is associated with skin lesions and cancer (Liu et al 2002).…”
mentioning
confidence: 99%
“…Clinical manifestations include hypopigmentation, keratosis, hypertension, cardiovascular diseases, diabetes, and even skin, lung and bladder tumoral pathologies [11]. Arsenicosis has been reported to occur in endemic areas with high level of As in drinking water or in burning coal [5,12]. A few cases of arsenicosis due to occupational exposure have also been reported, which probably is the result of reduction of methylation capacity in people who work in As contaminated workplaces [13].…”
Section: Arsenic Pollution and Arsenicosismentioning
confidence: 99%
“…Several villages in Southwest Guizhou Bouyei and Hmong Ethnic Autonomous Prefecture, China represent a unique case of endemic arseniasis, which is related with indoor combustion of high arsenic-content coal (Jin et al 2003;Zheng et al 2005;Liu et al 2002). The exposure in the endemic villages was given via a multiplex route, consisting of inhalation (Smith et al 2009;Pal et al 2007) of As-polluted indoor air, ingestion of As-contaminated food and, also possible, of direct skin penetration (Wester et al 2004;Lowney et al 2007).…”
Section: Introductionmentioning
confidence: 99%